Kimura’s Disease in Malaysian patients : three case reports - Roslan Abdul Rahman; Fadzilah Ismail; Roszalina Ramli; Ghazali Mat Nor; Sha Primuharsa Putra (penerbit ukm, 2005)
Kimura’s disease is a chronic inflammatory disorder which affects the subcutaneous tissues of the head and neck, axilla and upper limb as well as the groin region. In the head and neck region, major salivary glands and regional lymph nodes are mainly involved with associated eosinophilia and an elevated IgE concentration. Three cases of Kimura’s disease involving the parotid glands, lymph nodes and cheek are presented with a brief review of the literature.